2011
DOI: 10.1194/jlr.m007138
|View full text |Cite
|
Sign up to set email alerts
|

Contraction-induced skeletal muscle FAT/CD36 trafficking and FA uptake is AMPK independent

Abstract: Supplementary key words fatty acid metabolism • fatty acid translocase CD36 • traffi cking • AMP-dependent protein kinaseDuring submaximal exercise, plasma FAs are an important source of energy, accounting for ‫ف‬ 60% of total substrate utilization in human subjects ( 1-3 ). Increases in FA utilization during exercise are facilitated by a rapid and sustained upregulation of skeletal muscle FA uptake by 5-15-fold ( 1, 4 ). This increase in skeletal muscle FA uptake during exercise results from a coordinated inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 46 publications
5
70
1
Order By: Relevance
“…Prolonged light exposure decreased phosphorylation of CREB and AMPK, two main targets of β3-adrenergic signaling in the brown adipocyte. AMPK not only modulates intracellular lipolysis by phosphorylation of HSL, but also regulates uptake of lipids and glucose by inducing translocation of CD36, LPL, and GLUT4 to the plasma membrane (22,23), which may explain the reduced nutrient uptake by BAT. Moreover, we showed that in the absence of sympathetic input, BAT activity is equal among the various light-exposure groups.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged light exposure decreased phosphorylation of CREB and AMPK, two main targets of β3-adrenergic signaling in the brown adipocyte. AMPK not only modulates intracellular lipolysis by phosphorylation of HSL, but also regulates uptake of lipids and glucose by inducing translocation of CD36, LPL, and GLUT4 to the plasma membrane (22,23), which may explain the reduced nutrient uptake by BAT. Moreover, we showed that in the absence of sympathetic input, BAT activity is equal among the various light-exposure groups.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid spots were visualized with iodine vapor, and incorporated radioactivity was measured by liquid scintillation counting. FA uptake was determined as the sum of FA oxidation and incorporation, similar to methods described previously (17,20,30).…”
Section: Methodsmentioning
confidence: 99%
“…Isolated SOL muscles were incubated at 30°C in Krebs-Henseleit-Ringer buffer, pH 7.4, containing 2 mmol/L pyruvate, 2% FA-free BSA, and 0.5 mmol/L palmitic acid. After incubation at resting tension (4-5 mN) for 20 min, the incubation buffer was refreshed and supplemented with 0.5 mCi/mL [1- C] palmitate, as previously described (31). The incorporation of exogenous FAs into DAG and intracellular TAG was measured by thin-layer chromatography (TLC), as described below.…”
Section: Fa Oxidationmentioning
confidence: 99%